PENGARUH TERPAAN TAYANGAN YOUTUBE RUANG GURU DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA - Andre Indrawan; Diana Amaliasari; Dini Valdiani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2022)
This study aims to determine how much influence the Exposure of Ruang Guru Youtube Impressions as a medium of information on the learning activities of students of SMP Kamandaka Bogor. This study uses descriptive quantitative research methods. The sampling technique used in this study is Probality Sampling, the sample is determined using the Slovin formula and gets the number of respondents as many as 113 students. of 156 students total population. Ruang Guru's Youtube as an information medium is sufficient to provide a lot of information and insight about the world of education from the material presented on the Youtube channel which can be watched for free anywhere and anytime, with various kinds of playlists presented on the Ruang Guru Youtube channel. The learning activities of the students of SMP Kamandaka Bogor are still lacking in using the internet well but with good learning in schools. The results of this study indicate that there is an influence between exposure to the Ruang Guru Youtube show on the learning activities of the students of SMP Kamandaka Bogor. the results of the determination test showed that the exposure of Ruang Guru's Youtube shows had a contribution to the learning activities of students of SMP Kamandaka Bogor by 0.358. influenced by other factors. Further research is needed to explain these other reasons.